Analysis of FNAC in diagnosis of lymphadenopathy-a retrospective study from a regional cancer centre, Cuttack, Odisha - Pathy, Pramod Chandra; Hota, Subhransu Kumar; Dash, Sashibhusan; Samantaray, Sagarika; Panda, Sasmita; Rout, Niranjan (International Journal of Research in Medical Sciences, 2017)
Background: Lymphadenopathy is one of the most common clinical presentations and major causes of morbidity. Thus, clinical recognition and urgent diagnosis is of paramount importance. So, we aimed to analysis the diagnostic role of fine needle aspiration cytology (FNAC) in superficial lymphadenopathy in a regional cancer centre, Odisha, India. Methods: A total 1129 cases were retrieved from the hospital record retrospectively from the patients who had presented with superficial lymphadenopathy from January 2015 to December 2015. Results: Out of 1129 lymphadenopathy cases, 671 (59.43%) were male and 458 (40.56%) were female with male to female ratio 1.46:1. The age of the patients ranged from 4 years to 83 years with mean age 48.57 years. The most common site was observed in cervical lymph node 493 (43.66%) followed by submandibuar lymph nodes 198 (17.53%) and supraclavicular lymph nodes 172 (15.23%). 584 (51.27%) were malignant and 545 (48.27%) were benign. Reactive hyperplasia was most common 318 (58.34%) among benign cases where as metastatic squamous cell carcinoma was the most common 261 (50.77%) among malignant lesions. By FNAC all benign lesions were correctly diagnosed, and primary sites of malignancy identified in 442 (85.59%) cases. Cyto-histo correlation was done in 399 cases. The overall diagnostic accuracy of FNAC was found to be 93.98%, sensitivity 93.88%, specificity 94.64%, positive predictive value 99.8% and negative predictive value 71.62%. Conclusions: FNAC is a highly sensitive and specific tool for early detecting primary malignancy and metastatic lesions. Many inflammatory lesions can be treated based on FNAC alone.